FAZIA: a new performing detector for charged particles. (June 2020) - Barlini, S; Bini, M; Buccola, A; Camaiani, A; Casini, G; Ciampi, C; Frosin, C; Ottanelli, P; Pasquali, G; Piantelli, S; Poggi, G; Stefanini, A A; et al.
Abstract: The FAZIA apparatus is a new detector designed for the Fermi energy domain for charged particles based on three stages telescopes: Silicon detector (300 μm thick), Silicon detector (500 μm thick) and CsI(Tl) (10 cm). Using the ΔE-E technique and the Pulse Shape Analysis (PSA) it permits the charge and mass discrimination up to more than Z=20. In the following, some details about the FAZIA detectors and electronics, their performance and the frst experimental campaigns already performed will be discussed.